The Effect of a Combination of Hand Therapeutic Exercise and Hand Ball Exercise on Reducing Paresthesia Effects to Improve Functional Activity in the Wrist Area of the Elderly - Dewa Rahma Bhagaskara; Mianti Nirrizky Sutejo; Nana Noviada Kwartawaty; Deasy Virka Sari (Jurnal EduHealth, 2025)
Elderly individuals (aged >60 years) commonly experience physiological changes that affect various organ functions. In addition to physiological decline, biological factors such as decreased immune function also make them highly susceptible to degenerative diseases. Among these, neuromuscular disorders such as paraesthesia (tingling sensation) are frequently encountered. This study aimed to evaluate the effect of combining hand therapeutic exercise and hand ball exercise in reducing paraesthesia symptoms and improving functional activity in the wrist area of elderly individuals. This research used a quasi-experimental design with a one-group pre-test and post-test approach. The study involved elderly participants from a senior daycare community in Semarang. The Paired Sample Test yielded a significant result with a p-value of <0.001, indicating a statistically significant difference before and after the intervention. The combination of hand therapeutic exercise and hand ball exercise effectively reduces the symptoms of paraesthesia and improves wrist functional activity in elderly individuals.